Pharmacology, Toxicity, Bioavailability, and Formulation of Magnolol: An Update - Lin, Yiping; Li, Yuke; Zeng, Yuanlian; Tian, Bin; Qu, Xiaolan; Yuan, Qianghua; Song, Ying (Frontiers in Pharmacology, 2021)
Magnolol (MG) is one of the primary active components of Magnolia officinalis cortex, which has been widely used in traditional Chinese and Japanese herbal medicine and possesses a wide range of pharmacological activities. In recent years, attention has been drawn to this component due to its potential as an anti-inflammatory and antitumor drug. To summarize the new biological and pharmacological data on MG, we screened the literature from January 2011 to October 2020. In this review, we provide an actualization of already known anti-inflammatory, cardiovascular protection, anti-angiogenesis, anti-diabetes, hypoglycemic, antioxidation, neuroprotection, gastrointestinal protection and antibacterial activities of MG. Besides, results from studies on antitumor activity are presented. We also summarized the molecular mechanisms, toxicity, bioavailability and formulations of MG. Thereby we provide a valid cognition of MG.